It's always a women's problem!: Micro-entrepreneurs, work-family balance and economic crisis - Francesca Maria Cesaroni; Maria Gabriella Pediconi; Annalisa Sentuti (Administrative Sciences, 2018)
Gender inequality in the division of family work is vastly corroborated and work-family balance is an important topic in the female entrepreneurship field of research. Even if work-family balance should be a necessity indiscriminately perceived by all women and men who have a paid job, it is a particularly pertinent issue for women, called to find equilibrium between work and family. This study analyses the situation of men and women entrepreneurs in order to investigate how the economic crisis affected the work-family balance. A survey was conducted on a sample of 218 men and women sole-proprietors. Findings show that the work-family balance of women entrepreneurs does not seem to have been particularly affected by the crisis. However, some differences between men and women remain. Concerning balance, as expected, only women stated that they personally take care of the house and family. Different perceptions of the crisis between men and women also emerged, as a consequence of gender stereotypes. Women entrepreneurs have greater difficulty in having an internal psychological balance of the double role than men, who are more involved in the implementation of external balance and focus on corporate and social provisions.
Keywords: 350; work-family balance; female entrepreneurship; gender stereotypes; economic crisis; Italy